'As fezes que levar este feníssimo ouro': Una curiosa dedicatoria del Ms. LC P-152 de la Crónica do Imperador Beliandro. (2nd October 2021) - Álvarez-Cifuentes, Pedro
ABSTRACT: In this paper, I transcribe and analyse the dedication of a manuscript of Part I of the late chivalric romance Crónica do Imperador Beliandro, which is now preserved in the 'Portuguese Manuscripts Collection' at the Library of Congress (Washington). Following the tradition of specula principium or 'mirrors of princes', the dedication, dated 1692, recommends to the young António Estêvão da Costa e Sousa (1671-1723) the example of the chivalric heroes and alludes to emblematic literature (with some references to Andrés Laguna and Ammianus Marcellinus). This paper thus helps to reconstruct the textual history of this copy of the Crónica do Imperador Beliandro .